The laws of attraction: Economic drivers of inter-regional migration, housing costs and the role of policies - Causa, Orsetta (OECD Economics Department Working Papers, 2021)
This paper sheds light on inter-regional migration, housing and the role of policies, drawing on a new comparative cross-country approach. The results show that OECD countries exhibit stark variation in both levels and trends in inter-regional migration, which is found to be highly responsive to local housing and economic conditions. In turn, a large number of policies in the area of housing, labour markets, social protection and product markets influence the responsiveness of inter-regional migration to local economic conditions. For instance, more flexible housing supply makes inter-regional migration more responsive to local economic conditions while higher regulatory barriers to business start-ups and entry in professions significantly reduce the responsiveness of inter-regional mobility to local economic conditions. The capacity of workers to move regions in response to local economic shocks is one key dimension of labour market dynamism which could, at the current juncture, contribute to the recovery from the COVID-19 crisis. In this context, the paper proposes articulating structural with place-based policies to help prospective movers as well as stayers